Upaya Mewujudkan Kampung Iklim Melalui Program Bank Sampah dengan Partisipasi Aktif Masyarakat di Rejowinangun Selatan - Alifia Revan Prananda; Rhema Chandrawati; Dinda Kusumaningrum; Terbit Bagaskara Ahmad; Lidia Faridah (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2024)
In this modern era, handling environmental issues such as climate change and waste management is becoming increasingly crucial. The Waste Bank Program in South Rejowinagun plays a central role in the Climate Village initiative, aiming to increase community awareness of waste management through sorting and recycling. This initiative relies on active community participation to reduce the amount of waste sent to landfills and lower greenhouse gas emissions, thereby contributing to environmental cleanliness and climate change mitigation. Apart from positive ecological impacts, the Waste Bank also creates economic opportunities for the community by implementing a waste "savings" system, where each separated type has monetary value. The methods used, including lectures, counselling and training, are designed to educate the public, including PAUD children, about the importance of effective waste management. Although this program has shown positive results, challenges like a lack of public understanding remain. To overcome this and increase program effectiveness, a more intensive educational approach and strengthening collaboration networks between communities are needed.